Exploring Muslim Society knowledge on Wasiyyah in Baling, Kedah/ Siti Nabihah Ismail - Ismail, Siti Nabihah (2018)
Citizens in Malaysia especially Muslim are not aware about Islamic estate planning which is Wasiyyah (Isa, Othman, Azizan, Mohd Daud, 2017; Ghul, Yahya, & Abdullah, 2015). The issue arise when the individualities of unclaimed estates in the administration of the deceased's estate in Malaysia (Halim, 2017). Muslims in Malaysia are aware and familiar with the term Wasiyyah and its functions as mechanism in managing the inheritance in Islam. However, the issues on wealth of Wasiyyah property that are increasing year by year without proper distribution among the testator' beneficiary prove that the Wasiyyah issues in Malaysia is not a straight forward assignment (Zakiah, Khalid, Yaakob, Harun, & Hamid, 2016). It has been estimated that RM315 billion worth of asset had not been claimed by the heirs according to (Yusof, 2017). It shows the Muslims in Malaysia are refuse in well planning their wealth in serious matter. The study considered three variables, namely knowledge, purpose and benefit. First, knowledge about Wasiyyah which is to determine the understand among Muslim society. Second, purpose of preparing Wasiyyah which is to deterrmine the reasons of Muslim society in having Wasiyyah. Third, benefit of Wasiyyah which is to identify the benefits of having Wasiyyah for Muslim. This study will use primary data and questionnaire will be distributed to 100 respondents in Baling, Kedah. The main methodology is regression analysis. The research is expected to reveal significant influence of knowledge of Wasiyyah among the respondents significant influence of purpose of Wasiyyah and significant benefits of Wasiyyah.